Pengaruh Tingkat Suku Bunga SBI, Rating, Likuiditas dan Maturitas terhadap Yield to Maturity Obligasi - INDARSIH, NANIK (Jurnal Ilmu Manajemen (JIM), 2013)
An investors who will invested their fund in bonds securities should pay attention of bond yields because the yields can provide information of the benefit to be received on the funds invested. This study aimed to analyze the influence of SBI rate, rating, liquidity and maturity on corporate bonds yield. Bond yield is measured using the method of Yield To Maturity (YTM). Samples taken in this study consisted of 30 financial sector of corporate bonds listed in Indonesia Stock Exchange from 2007 to 2010. Data is analyzed using multiple regression analysis techniques. The results of this study showed variables SBI rate and maturity has a positive effect on Yield To Maturity. Variables rating and liquidity does not affect the Yield To Maturity of corporate bonds. Keywords: Yield To Maturity, SBI rate, rating, liquidity